The tetranucleotide UCAY directs the specific recognition of RNA by the Nova K-homology 3 domain - Jensen, Kirk B. (The National Academy of Sciences, 2000)
The Nova family of proteins are target antigens in the autoimmune disorder paraneoplastic opsoclonus-myoclonus ataxia and contain K-homology (KH)-type RNA binding domains. The Nova-1 protein has recently been shown to regulate alternative splicing of the α2 glycine receptor subunit pre-mRNA by binding to an intronic element containing repeats of the tetranucleotide UCAU. Here, we have used selection-amplification to demonstrate that the KH3 domain of Nova recognizes a single UCAY element in the context of a 20-base hairpin RNA; the UCAY tetranucleotide is optimally presented as a loop element of the hairpin scaffold and requires protein residues C-terminal to the previously defined KH domain. These results suggest that KH domains in general recognize tetranucleotide motifs and that biological RNA targets of KH domains may use either RNA secondary structure or repeated sequence elements to achieve high affinity and specificity of protein binding.